Video systems in an IT environment : the essentials of professional networked media - Kovalick, Al (Elsevier/Focal Press, 2006)
Audio/Video (AV) systems and Information Technology (IT) are colliding. Broadcasters and other AV professionals are impacted by the transition to IT components and techniques. This is the first book to focus on the intersection of AV and IT concepts. It includes technology reviews and the tools to understand and evaluate key aspects of hybrid AV systems. Twelve chapters encompass a broad range of information including: IT integration, AV networking, storage systems, file and metadata formats, software platforms, reliability, element management, security, workflow improvement, AV technology, t.